Leadership and transformational change in healthcare organisations: A qualitative analysis of the North East Transformation System. (February 2013) - Erskine, Jonathan; Hunter, David J; Small, Adrian; Hicks, Chris; McGovern, Tom; Lugsden, Ed; Whitty, Paula; Steen, Nick; Eccles, Martin Paul
The research project 'An Evaluation of Transformational Change in NHS North East' examines the progress and success of National Health Service (NHS) organisations in north east England in implementing and embedding the North East Transformation System (NETS), a region-wide programme to improve healthcare quality and safety, and to reduce waste, using a combination of Vision, Compact, and Lean-based Method. This paper concentrates on findings concerning the role of leadership in enabling tranformational change, based on semi-structured interviews with a mix of senior NHS managers and quality improvement staff in 14 study sites. Most interviewees felt that implementing the NETS requires committed, stable leadership, attention to team-building across disciplines and leadership development at many levels. We conclude that without senior leader commitment to continuous improvement over a long time scale and serious efforts to distribute leadership tasks to all levels, healthcare organisations are less likely to achieve positive changes in managerial-clinical relations, sustainable improvements to organisational culture and, ultimately, the region-wide step change in quality, safety and efficiency that the NETS was designed to deliver.